ANALYSING THE INFLUENCE OF ELECTRONIC WORD OF MOUTH (EWOM) AND SOCIAL MEDIA INFLUENCER ON PURCHASE INTENTION FOR CULINARY BUSINESSES AT FLAMBOYAN STREET MANADO - Wijaya, Kanaya; Lapian, S. L. H. V. Joyce; Tielung, Maria V. J. (Universitas Sam Ratulangi, 2024)
Social media can be utilized as a cost-effective digital marketing method, and can quickly increase the popularity of a business. Through social media, customers can share their experiences in using products/services from a company which are expressed in various forms, including in the form of audio, video, and writing such as comments and reviews from customers to tell the product or service to others by online in order to increase purchase intention. This study aims to analyze the influence of Electronic Word of Mouth (eWOM) and Social Media Influencer on purchase intention in culinary businesses on Flamboyan Street, Manado. The research method used is quantitative with a sample size of 150 Gen Z and Millennials who actively use social media. The data collection method was carried out through a questionnaire with a Likert scale. Data analysis methods include classical assumption testing, multiple linear regression analysis, hypothesis testing using the t test and F test. The research results show that eWOM and influencers have a significant impact on consumer purchasing intention in culinary businesses on Flamboyan Street, Manado. Keyword: Electronic Word of Mouth (eWOM), Social Media Influencer, Purchase Intention